Bridging the gap: the OPTIONS program as a model for integrating career development into biomedical PhD training - Neely, Crystal J.; Abras, Chadia; Lauka, Bri; Oladeinde, Moremi; Eith, Christine A. (Frontiers in Education, 2025)
The OPTIONS program employs an innovative approach to integrating career readiness into the foundation of biomedical doctoral education. Designed to address the growing need for diverse career pathways beyond academic roles, this three-phase program provides structured opportunities for PhD students to explore career interests, develop transferable skills, and participate in experiential learning opportunities prior to graduating. Over the past 6 years, the program has experienced substantial growth, currently supporting over 300 doctoral students and with ~50 alumni who have transitioned into careers across academia, industry, government, and other sectors. Preliminary findings suggest that participating in the OPTIONS program improves students’ ability to articulate how their graduate training translates to career opportunities and enhances their awareness of actionable steps to develop career-related skills. By embedding career development into doctoral education and addressing evolving workforce demands, OPTIONS represents a scalable model for equipping graduates to thrive in today’s dynamic and multidisciplinary professional landscape.